2011
DOI: 10.1038/npre.2011.6001.1
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli EHEC Germany outbreak preliminary functional annotation using BG7 system

Abstract: We have annotated the European outbreak E. coli EHEC genome sequenced by BGI (6-2-2011) and assembled with MIRA by Nick Loman (6-2-2011 ). Our system BG7, Bacterial Genome annotation of Era7 Bioinformatics, predicts ORFs and annotates them based on fragments of similarity with Uniprot proteins. We have predicted 6327 genes, 6156 encoding proteins y 171 corresponding to ribosomal and tRNA. Based on the preliminary results of our semi-automated method of annotation we have selected some predicted proteins with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This information is relevant to understanding of the role that the horizontal gene exchange plays in evolution of new pathogens. The analysis of the complete genome sequence of the strain E. coli TY-2482 isolated from the latest outbreak of entero-aggregative-haemorrhagic (EAHEC) infection in Europe in 2011 showed that its extraordinary virulence and lethality are associated with the virulence determinants located in horizontally transferred GIs (Brzuszkiewicz, 2011); (Manrique, 2011). Enterobacteria (Escherichia, Shigella and Salmonella) share multiple GIs shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This information is relevant to understanding of the role that the horizontal gene exchange plays in evolution of new pathogens. The analysis of the complete genome sequence of the strain E. coli TY-2482 isolated from the latest outbreak of entero-aggregative-haemorrhagic (EAHEC) infection in Europe in 2011 showed that its extraordinary virulence and lethality are associated with the virulence determinants located in horizontally transferred GIs (Brzuszkiewicz, 2011); (Manrique, 2011). Enterobacteria (Escherichia, Shigella and Salmonella) share multiple GIs shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy, speed and specificity of BG7 for NGS projects were proved in a real case, the 2011 Germany E. coli outbreak [17]. BG7 annotations for all the sequenced isolates can be found at: https://github.com/ehec-outbreak-crowdsourced/BGI-data-analysis/tree/master/strains.…”
Section: Introductionmentioning
confidence: 99%